Nutrition related health status and associated factors in juvenile male and female on remand detainees at entry into Pollsmoor correctional service facility in the Western Cape - Theron Marieke (Department of Human Biology, 2021)
Background: International and national (South African constitution) laws mandate that the Department of Correctional Services (DCS) ensure that on remand detainees receive the same medical treatment as those who are not incarcerated, as well as adequate nutrition while incarcerated. Literature across the globe indicates that inmates are at an increased risk of health problems and malnutrition, with juveniles being at an even higher risk than the adult inmate population. To our knowledge no research on the nutritional status of juveniles at entry into correctional facilities in South Africa or internationally has been published to date. The aim of this research was to determine and compare the nutrition related health status, associated factors and predictors in juvenile male and female on remand detainees at entry into Pollsmoor correctional service facilities in the Western Cape. Methods: In this cross-sectional comparative study of 67 male and 52 female juvenile on remand detainees the following was assessed using an interviewer based questionnaire: sociodemographic information including age, ethnicity, language spoken at home, a hunger score, meal pattern and food choices in the week prior to entry into the facility using a nonquantified FFQ, understanding of healthy eating, physical activity and sedentary behaviour before entry using the GPAQv2, risk taking behaviours (smoking and alcohol an illicit substance use), body shape perception, and symptoms of depression and anxiety using the K10 tool. The following physical measures were taken: weight, height, triceps-skinfold, mid-upper arm circumference (MUAC) and maximum handgrip strength (MHGS). BMI and the corrected arm muscle area (cAMA) were calculated. All variables were analysed descriptively and compared between male and female juveniles using Pearson Chi-square test, independent samples t-test or Mann-Whitney U test as appropriate. Association tests (Spearman Rank correlation coefficient for continuous and cross-tabulations and the Pearson's Chi square test for categorical variables) were furthermore undertaken with BMI, cAMA and MHGS as the dependent variables within each gender group. The same tests were used to conduct association analysis between socio-demographic variables, dietary intake, physical activity, risk taking behaviour and symptoms of depression and anxiety within each gender group. Multiple linear regression analyses were conducted to identify predictors of BMI, cAMA and MHGS within each gender groups. The clinical significance of statistically significant predictors was assessed using novel criteria. 4 Results: A summary of the profiles of juvenile female and male on remand detainees are shown in Table A, while the predictors of malnutrition in the same population are shown in Table B following the abstract conclusion. Juvenile female on remand detainees were characterised by a double burden of malnutrition, namely undernutrition (15.4%) and overweight/obesity (23.1%). Coloured (55.8%) and black African ethnicities (42.3%) were equally represented in the sample, with Afrikaans being the most common (46.2%) and isiXhosa the second most common home language reported (32.7%). Only a few had completed grade 12, and half had given birth to one or more children. Food insecurity was reported by 30.8%. Food choices showed frequent intake of low nutrient high-energy food items (table sugar, crisps, white bread, fizzy drinks that contain sugar and non-fibre containing starches) and less frequent intake of nutrient dense foods (fruits, vegetables, dairy and quality proteins). Physical activity levels were high (67.3% classified as active with ≥3000 MET minutes/week), with walking/cycling to get to places being a major contributor to time spent doing physical activity median (IQR) 106 (51-300) minutes/day. Daily illicit substance use was the most common risk taking behaviour, especially amongst the females from the coloured ethnic group (48%). Daily smoking was also common, also specifically amongst those from the coloured ethnic group (83%), while alcohol use seemed to be less prominent. Female detainees were also characterized by the presence of depression and anxiety symptoms (74.5% moderate to very high score). The prevalence of infectious disease was reportedly low (13.7%), but may have been an underestimation Juvenile male on remand detainees were characterised by undernutrition (17.9%), but none of them were overweight or obese. The majority of males were from the coloured ethnic group (65.7%) and reported that they had Afrikaans as home language (65.7%). As was the case for the females, only a few had completed grade 12. Food insecurity was reported by 43.3%. Similar to females, food choice data showed frequent intake of low nutrient high-energy food items and less frequent intake of nutrient dense foods. Physical activity levels were high (83.6% active with ≥3000 MET min/week), with both walking/cycling to get to places (60 min/day) and recreational physical activity (26 min/day) contributing to time spent doing physical activity. Smoking was the most common risk taking behaviour followed by illicit substance use (smoking was highest in the coloured males 82%). Both smoking and illicit substance use was more frequent in the male sample, while daily alcohol intake was not common in either gender. Male detainees were also characterized by the presence of depression and anxiety symptoms (74.6%) that were positively associated with illicit substance use. As for females, the prevalence of infectious disease was reportedly low (9%). 5 Predictors of probable clinical significance for juvenile female on remand detainees were as follows: BMI - frequency of vegetable intake (+), frequency of high-fat snack intake (+), frequency of dairy food intake (-), illicit substance use (-), physical activity in MET minutes (-) and availability of fruit juice in the home (-); cAMA - having Afrikaans as home language and depression and anxiety symptoms (-); and MHGS having Afrikaans as home language (-) and anxiety and depression symptoms (-). Predictors of probable clinical significance juvenile male on remand detainees were as follows: BMI -having Afrikaans as home language (-); cAMA - frequency of snacking between meals per week (+) and having Afrikaans as home language (-); and MHGS - hunger score (-) and having Afrikaans as home language or isiXhosa as home language (-). Conclusions and recommendations: The key conclusion of this research is that both female and male juveniles were prone to be malnourished at admission to the correctional facility (Pollsmoor correctional facility). Females had a double burden of malnutrition, with both underweight and overweight/obesity being present, while underweight was the key malnutrition problem in males. It can further be concluded that being from the coloured ethic group and having Afrikaans as a home language increased the risk of being underweight at admission to the correctional facility for both male and female on remand detainees. For female detainees it can be concluded that low frequency of intake of vegetables, high levels of physical activity, frequent use of illicit substances and the presence of depression and anxiety in the month preceding the study also increased the risk of being undernourished, while greater frequency of consumption of high fat snacks increased the risk for being overweight/obese. For male detainees it can be concluded that food insecurity and lower snacking between meals also increased the risk of being undernourished. The main recommendation from this study is for the Department of Correctional Services (DCS) to implement a nutritional status screening procedure at the point of entry of a juvenile into a correctional facility for identification/diagnosis of nutrition related problems and associated factors for referral for nutrition and other health support within the facility.